Performance of Different Hybirds of Maize with Different Times and Methods of Sowing - Khan, R.A.; Tripathi, R.S.; Malik, D.S. (Journal of Soil and Water Conservation, 2022)
Paddy, wheat and other food grain crops cannot compete with hybrid maize for grain production per unit area. A good crop of hybrid maize with judicious manuring can yield on an average 50-60 quintals or even more of grain/ ha. Water unlike in case of wheat and paddy is not a limiting factor for maize crop as it matures with rains. Hybrid maize is also capable of producing concentrates and feed for huge cattle population. Production of hybrid maize in India and other semi-developed countries could help to a great extent for tiding over the acute food problem.